Kapò - Solinas, Franco 1927-1982 (Criterion Collection, 2010)
The story of a Jewish girl from Paris sent to a concentration camp during World War II and her struggle to survive by stealing another's identity and becoming a warden
DVD; NTSC, region 1; 1.66:1 aspect ratio; monaural. - Originally produced as a motion picture in 1959. - Title on container: Janus Films presents Essential art house : Kapò
Susan Strasberg, Laurent Terzieff, Emanuelle Riva
Music, Carlo Rustichelli ; cinematography, Alexandar Sukulovic ; editing, Roberto Cinquini